Excavations at Saraçhane in Istanbul. - Harrison, R. M. (R. Martin), 1935- (Princeton legacy library., 1986)
This work is the first volume of two that will be the full report of major excavations carried out by Dumbarton Oaks and the Istanbul Archaeological Museum at Sarachane in the heart of ancient Constantinople. This volume includes discussion of excavation and stratigraphy; catalogs of sculpture, revetment, mosaic, small finds and other materials: and general treatment of architecture, sculpture, and history of the site. Originally published in 1986. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distingui.